2017
DOI: 10.4236/ojo.2017.71002
|View full text |Cite
|
Sign up to set email alerts
|

Primary Alveolar Soft Part Sarcoma of the Scapula

Abstract: Alveolar soft-part sarcoma (ASPS) is an uncommon, aggressive soft-tissue neoplasm, occurring in less than 1% of sarcomas. It is typically found in the head and neck tissues in children or in the deep soft tissues of the lower extremities in young adults. This tumor arises primarily within the skeletal muscles or musculofascial planes. Primary involvement of bone is extremely rare. ASPS has poor prognosis with a propensity for recurrence as well as distant metastasis. In this report, we present a 25-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Very few cases have been reported in scapular region. Authors found that tumor presented with bony erosion and poorly defined tumor margins [10][11][12][13] and their relevant findings were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few cases have been reported in scapular region. Authors found that tumor presented with bony erosion and poorly defined tumor margins [10][11][12][13] and their relevant findings were summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…For ASPS prognostic risk factors are age >10 years, tumor size >5cm and presence of distant metastases. 7,9,12,13 Surgical excision remains the primary modality of treatment for ASPS. In advance disease, it may be followed by adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%